FGL2 promotes tumor progression in the CNS by suppressing CD103+ dendritic cell differentiation - Yan, Jun; Zhao, Qingnan; Gabrusiewicz, Konrad; Kong, Ling-Yuan; Xia, Xueqing; Wang, Jian; Ott, Martina; Xu, Jingda; Davis, R. Eric; Huo, Longfei; Rao, Ganesh; Sun, Shao-Cong; et al. (Nature communications, 2019)
Few studies implicate immunoregulatory gene expression in tumor cells in arbitrating brain tumor progression. Here we show that fibrinogen-like protein 2 (FGL2) is highly expressed in glioma stem cells and primary glioblastoma (GBM) cells. FGL2 knockout in tumor cells did not affect tumor-cell proliferation in vitro or tumor progression in immunodeficient mice but completely impaired GBM progression in immune-competent mice. This impairment was reversed in mice with a defect in dendritic cells (DCs) or CD103 + DC differentiation in the brain and in tumor-draining lymph nodes. The presence of FGL2 in tumor cells inhibited granulocyte-macrophage colony-stimulating factor (GM-CSF)-induced CD103 + DC differentiation by suppressing NF-κB, STAT1/5, and p38 activation. These findings are relevant to GBM patients because a low level of FGL2 expression with concurrent high GM-CSF expression is associated with higher CD8B expression and longer survival. These data provide a rationale for therapeutic inhibition of FGL2 in brain tumors. Fibrinogen-like protein 2 (FGL2) mediates immune suppression in glioblastoma (GBM). Here, the authors show that FGL-2 expressed by GBM cancer cells acts by suppressing the differentiation of CD103+ DC cells required to activate the anti-tumor CD8+ T cell response via blocking GM-CSF signalling at NFKB, STAT1/5 and p38 level.